Understanding the process and benefits of tree-planting campaign for environmental sustainability - Hussin, Muhammad Rosni Amir; Halimah@Nasibah, Ahmad; Aripin, Norhani; Amran, Noor Afza; Khusaini, Zulitha Arina (Journal of Islamic, Social, Economics and Development, 2025)
Environmental sustainability is a pressing global concern due to the effects of climate change on health, ecosystems, and economies. In response, Malaysian government agencies and private companies have engaged in tree-planting initiatives as part of their corporate social responsibility (CSR) efforts. In 2022, Telekom Malaysia (TM), a telecommunications company, launched a tree-planting campaign through its foundation, Yayasan Telekom Malaysia (YTM), involving multiple stakeholders across various locations. This study explores the process and benefits of YTM's tree-planting campaign, addressing a critical gap in research on practical environmental sustainability initiatives. Prior studies have primarily focused on reporting environmental elements in sustainability reports required by Bursa Malaysia, often using quantitative approaches. In filling the research gap, this study employed a qualitative approach, using semi-structured interviews as the main instrument to examine environmental sustainability practices through a tree-planting campaign. The findings outline the planning and execution process for tree planting and enumerate the campaign's benefits, such as its contributions to environmental sustainability and raising awareness of Malaysia's tree heritage. The results demonstrate that the telecommunications company successfully executed the campaign and achieved its objectives.